The Development of Liveworksheet-Assisted Problem Based Learning Teaching Materials to Improve Students' Learning Outcomes on Social Arithmetic - Ramdani, Rasya Asri; Amelia, Risma ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
This study intends to determine the feasibility and practicality of worksheets for students of Social Arithmetic material using the Liveworksheets-assisted Problem Based Learning learning model. The development model used is the 4D method which is limited to the third step which includes: define, design and develompment stages. Feasibility test data and practicality of LKPD were collected through observation and questionnaires. The feasibility of LKPD is analyzed based on the results of validation by experts and the practicality of LKPD seen from student questionnaire responses. The subjects of this study were 5 students on a small scale and 30 students on a broad scale. The results of this study show that the LKPD tested is very feasible and very practical to use for learning. This is seen based on the results of validation by experts who get an average of 95% with very valid categories and the practicality of LKPD taken from student response questionnaires with a percentage of 87.56% on a small scale and 88.33% on a broad scale. This shows that LKPD uses the Liveworksheets-assisted Problem Based Learning learning model on Social Arithmetic material is very valid and practical to use.